Extreme Weather, Climate and Natural Disasters in Ireland - Ludlow, Francis (Environmental Protection Agency, 2010)
The aim of this project was to collate historical, proxy and observational (recent) records, and analyse the information within this variety of sources for incidences of extreme weather events and natural disasters, which may give insight into the variability of climate in Ireland, and its impact on human society. The study focused on extreme weather conditions: historical analysis from the fifth through to the seventeenth century ad was derived from the Gaelic Annals of Ireland and also from local and regional proxy data (e.g. tree rings and ice-core data). Observational data from the nineteenth century onwards was analysed to identify extremes in rainfall, winds, storms, floods and droughts.
PUBLISHED
Climate change, history, impacts and adaptation in Ireland.
Johnstown Castle, Wexford
Keywords: Climate change; Climate history; Climate change impacts; Irish climate; Digital Humanities; Making Ireland; Manuscript, Book and Print Cultures; Smart & Sustainable Planet; CLIMATE CHANGE; CLIMATE-CHANGE; Climate Change; Climate Change; Climate Change; Climate Change; Climate Change Impacts on the Environment; Climate History; Coastal Meteorology; Irish History; Irish climate; Meteorology; Meteorology; Meteorology; Natural Hazards; climate change impacts; extreme weather